Use Laplace transform to solve the following initial-value problem y"+2y'+y=0 y(0)=1, y'(0)=1 a) displaystyle{e}^{{-{t}}}+{t}{e}^{{-{t}}} b) displaystyle{e}^{t}+{2}{t}{e}^{t} c) displaystyle{e}^{{-{t}}}+{2}{t}{e}^{t} d) displaystyle{e}^{{-{t}}}+{2}{t}{e}^{{-{t}}} e) displaystyle{2}{e}^{{-{t}}}+{2}{t}{e}^{{-{t}}} f) Non of the above

Question
Laplace transform
asked 2021-02-19
Use Laplace transform to solve the following initial-value problem
\(y"+2y'+y=0\)
\(y(0)=1, y'(0)=1\)
a) \displaystyle{e}^{{-{t}}}+{t}{e}^{{-{t}}}\)
b) \displaystyle{e}^{t}+{2}{t}{e}^{t}\)
c) \displaystyle{e}^{{-{t}}}+{2}{t}{e}^{t}\)
d) \displaystyle{e}^{{-{t}}}+{2}{t}{e}^{{-{t}}}\)
e) \displaystyle{2}{e}^{{-{t}}}+{2}{t}{e}^{{-{t}}}\)
f) Non of the above

Answers (1)

2021-02-20
Step 1
Given initial value problem,
\(y''+2y'+y=0\)
\(y(0)=1\)
\(y'(0)=1\)
Step 2
Taking inverse Laplace transform,
\(\displaystyle{L}{\left[{y}{''}+{2}{y}'+{y}\right]}={0}\)
\(\displaystyle{L}{\left[{y}{''}\right]}+{2}{L}{\left[{y}'\right]}+{L}{\left[{y}\right]}={0}\)
Use the formula such that,
\(\displaystyle{L}{\left[{y}{''}\right]}={s}^{2}{L}{\left[{y}\right]}-{s}{y}{\left({0}\right)}-{y}'{\left({0}\right)}\)
\(\displaystyle{L}{\left[{y}'\right]}={s}{L}{\left[{y}\right]}-{y}{\left({0}\right)}\)
Then,
\(\displaystyle{s}^{2}{L}{\left[{y}\right]}-{s}{y}{\left({0}\right)}-{y}'{\left({0}\right)}+{2}{\left[{s}{L}{\left[{y}\right]}-{y}{\left({0}\right)}\right]}+{L}{\left[{y}\right]}={0}\)
\(\displaystyle{s}^{2}{L}{\left[{y}\right]}-{s}-{1}+{2}{\left[{s}{L}{\left[{y}\right]}-{1}\right]}+{L}{\left[{y}\right]}={0}\)
\(\displaystyle{s}^{2}{L}{\left[{y}\right]}-{s}-{1}+{2}{s}{L}{\left[{y}\right]}-{2}+{L}{\left[{y}\right]}={0}\)
\(\displaystyle{\left({s}^{2}+{2}{s}+{1}\right)}{L}{\left[{y}\right]}-{s}-{3}={0}\)
\(\displaystyle{L}{\left[{y}\right]}=\frac{{{s}+{3}}}{{{s}^{2}+{2}{s}+{1}}}\)
Step 3
Taking inverse Laplace transform of both sides,
\(\displaystyle{y}={L}^{ -{{1}}}{\left[\frac{{{s}+{3}}}{{{s}^{2}+{2}{s}+{1}}}\right]}\)
\(\displaystyle={L}^{ -{{1}}}{\left[\frac{{{s}+{1}}}{{\left({s}+{1}\right)}^{2}}+\frac{2}{{\left({s}+{1}\right)}^{2}}\right]}\)
\(\displaystyle={L}^{ -{{1}}}{\left[\frac{1}{{{s}+{1}}}\right]}+{2}{L}^{ -{{1}}}{\left[\frac{1}{{\left({s}+{1}\right)}^{2}}\right]}\)
\(\displaystyle={e}^{{-{t}}}+{2}{t}{e}^{{-{t}}}\)
Step 4
Hence, the solution of given initial value problem is
\(\displaystyle{y}{\left({t}\right)}={e}^{{-{t}}}+{2}{t}{e}^{{-{t}}}\)
0

Relevant Questions

asked 2021-02-08
Use the Laplace transform to solve the following initial value problem:
\(2y"+4y'+17y=3\cos(2t)\)
\(y(0)=y'(0)=0\)
a)take Laplace transform of both sides of the given differntial equation to create corresponding algebraic equation and then solve for \(L\left\{y(t)\right\}\) b) Express the solution \(y(t)\) in terms of a convolution integral
asked 2021-03-04
use the Laplace transform to solve the given initial-value problem.
\(y"+y=f(t)\)
\(y(0)=0 , y'(0)=1\) where
\(\displaystyle f{{\left({t}\right)}}={\left\lbrace\begin{matrix}{1}&{0}\le{t}<\frac{\pi}{{2}}\\{0}&{t}\ge\frac{\pi}{{2}}\end{matrix}\right.}\)
asked 2021-02-09
In an integro-differential equation, the unknown dependent variable y appears within an integral, and its derivative \(\frac{dy}{dt}\) also appears. Consider the following initial value problem, defined for t > 0:
\(\frac{{{\left.{d}{y}\right.}}}{{{\left.{d}{t}\right.}}}+{4}{\int_{{0}}^{{t}}}{y}{\left({t}-{w}\right)}{e}^{{-{4}{w}}}{d}{w}={3},{y}{\left({0}\right)}={0}\)
a) Use convolution and Laplace transforms to find the Laplace transform of the solution.
\({Y}{\left({s}\right)}={L}{\left\lbrace{y}{\left({t}\right)}\right)}{\rbrace}-?\)
b) Obtain the solution y(t).
y(t) - ?
asked 2021-03-07
use the Laplace transform to solve the initial value problem.
\(y"-3y'+2y=\begin{cases}0&0\leq t<1\\1&1\leq t<2\\ -1&t\geq2\end{cases}\)
\(y(0)=-3\)
\(y'(0)=1\)
asked 2021-01-22
Use Laplace transform to solve the folowing initial value problem \(y"+2y'+y=4e^{-t} y(0)=2 y'(0)=-1\)
asked 2021-01-30
Use Laplace transform to find the solution of the IVP
\(2y'+y=0 , y(0)=-3\)
a) \(f{{\left({t}\right)}}={3}{e}^{{-{2}{t}}}\)
b)\(f{{\left({t}\right)}}={3}{e}^{{\frac{t}{{2}}}}\)
c)\(f{{\left({t}\right)}}={6}{e}^{{{2}{t}}}
d) \(f{{\left({t}\right)}}={3}{e}^{{-\frac{t}{{2}}}}\)
asked 2021-02-21
Find the Laplace transforms of the following time functions.
Solve problem 1(a) and 1 (b) using the Laplace transform definition i.e. integration. For problem 1(c) and 1(d) you can use the Laplace Transform Tables.
a)\(f(t)=1+2t\) b)\(f(t) =\sin \omega t \text{Hint: Use Euler’s relationship, } \sin\omega t = \frac{e^(j\omega t)-e^(-j\omega t)}{2j}\)
c)\(f(t)=\sin(2t)+2\cos(2t)+e^{-t}\sin(2t)\)
asked 2020-12-17
use the Laplace transform to solve the given initial-value problem. \(y"+y'-2y=10e^{-t}, y(0)=0,y'(0)=1\)
asked 2020-12-06
Use the Laplace transform to solve the given initial-value problem.
\(\displaystyle{y}{''}+{8}{y}'+{41}{y}=\delta{\left({t}-\pi\right)}+\delta{\left({t}-{3}\pi\right)},\ \ \ \ {y}{\left({0}\right)}={1},\ \ \ \ {y}'{\left({0}\right)}={0}\ \ {y}{\left({t}\right)}=?\)
asked 2021-02-08
Find the inverse Laplace transform of \(F(s)=\frac{(s+4)}{(s^2+9)}\)
a)\(\cos(t)+\frac{4}{3}\sin(t)\)
b)non of the above
c) \(\cos(3t)+\sin(3t)\)
d) \(\cos(3t)+\frac{4}{3} \sin(3t)\)
e)\(\cos(3t)+\frac{2}{3} \sin(3t)\)
f) \(\cos(t)+4\sin(t)\)
...